Religion, culture and illness: a sociological study on religious coping in Iran - Ahmadi, Fereshteh (Mental health, religion & culture, 2018)
The present article is based on an international study on meaning-making coping aimed at understanding the role of culture in coping. The larger study has been conducted among cancer patients in 10 countries. The present article is confined to the results obtained in our study in Iran and restricted to religious coping methods. Twenty-seven participants with various kinds of cancer were interviewed. The several religious coping methods found in the present study are categorised on the basis of RCOPE’s five basic religious functions. The study reveals, among others, the impact of cultural beliefs on certain religious coping methods, even among those who are not regarded as practicing Muslims. The study highlights the importance of investigating cultural and social context when exploring the use of the meaning-making coping strategies in different countries.